Halogenated monopyridinium oximes are less effective in reactivation of phosphylated cholinesterases than bisquaternary oximes - Kohoutova, Zuzana; Prchalova, Eliska; Andrys, Rudolf; Knittelova, Karolina; Formanova, Marketa; Hofmanova, Tereza; Psotka, Miroslav; Musilek, Kamil; Derat, Etienne; Malinak, David (Bioorganic chemistry, 2024)
Mono-quaternary pyridinium oximes derived from K-oximes K027, K048 and K203 were designed, synthesized and evaluated for the reactivation of organophosphate-inhibited cholinesterases. The incorporation of the halogen atoms to the structure decreased the pKa value of the oxime group resulting in an increased formation of oximate necessary for reactivation. The stability and pKa values were found to be similar to analogous bis-quaternary compounds. Some mono-quaternary oximes resulted as relatively strong inhibitors of human acetylcholinesterase. Nevertheless, the reactivation ability of mono-quaternary oximes for organophosphate-inhibited cholinesterases was lower compared to their bis-quaternary analogues. These results were further confirmed by the determination of reactivation kinetics, when in some cases novel compounds showed improvement reactivation compared to the tested standards, but no improvement to bis-quaternary K-oximes. A computational study investigated reactivation process for K027, and its two analogues for VX-inhibited AChE. This study revealed slight differences between reactivation of mono-quaternary and bis-quaternary oximes. Abbreviations: 2-PAM, pralidoxime; AChE, acetylcholinesterase; ACN, acetonitrile; ATCI, acetylcholine iodide; BChE, butyrylcholinesterase; BTCI, butyrylcholine iodide; Bu3SnSnBu3, bis(tributyltin) Et2O, diethyl ether; ChEs, cholinesterases; CNS, central nervous system; DAD, diode array detector; DIBAL-H, diisobutylaluminium hydride; DMF, dimethylformamide; DMSO, dimethyl sulfoxide; DTNB, 5,5́-dithiobis-2-nitrobenzoic acid; Et3N, triethylamine; EtOAc, ethyl acetate; EWG, electron withdrawing group; HI-6, asoxime; hrAChE, human recombinant acetylcholinesterase; hrBChE, human recombinant butyrylcholinesterase; hrChEs, human recombinant cholinesterases; HPLC, high-performance liquid chromatography; HRMS, high-resolution mass spectrometry; KD, dissociation constant; kr, first-order reactivation rate constant; kr2, second-order reactivation rate constant; LüH-6, obidoxime; MeOH, methanol; MM, molecular mechanics; MMC-4, methoxime; m.p., melting point; NCIs, non-covalent interactions; NEDPA, 4-nitrophenyl ethyl dimethylphosphoramidate; NEMP, 4-nitrophenyl ethyl methylphosphonate; NIMP, isopropyl methylphosphonate; NMR, nuclear magnetic resonance spectroscopy; OPs, organophosphates; PBS, phosphate-buffered saline; Pd(dppf)Cl2.CH2Cl2, [1,1'-Bis(diphenylphosphino)ferrocene]dichloropalladium(II) in complex with dichloromethane; pKa, negative decimal logarithm of the dissociation constant; POX, paraoxon; PPh3, triphenylphosphine; QM, quantum mechanics; rt, room temperature; SN2, bimolecular nucleophilic substitution; SNAc, nucleophilic acyl substitution; THF, tetrahydrofuran; TMC-4, trimedoxime; TNB, 5-thio-2-nitrobenzoic acid; UHPLC, ultra high-performance liquid chromatography; UV, ultraviolet; UV-VIS, ultraviolet-visible.
Keywords: kinetika; Dose-Response Relationship, Drug; pyridinové sloučeniny; Reactivation; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; Cholinesterase Reactivators; Butyrylcholinesterase; cholinesterasové inhibitory; acetylcholinesterasa; Inhibition; butyrylcholinesterasa; lidé; Organophosphate; Cholinesterase Inhibitors; Oximes; Pyridinium Compounds; Halogenation; vztahy mezi strukturou a aktivitou; Humans; Kinetics; Oxime; molekulární struktura; Cholinesterase; Structure-Activity Relationship; oximy; reaktivátory cholinesterasy; halogenace; Molecular Structure